2015
DOI: 10.11646/zootaxa.3947.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of the hairy long-nosed armadillo “Dasypus” pilosus (Xenarthra, Dasypodidae) and revalidation of the genus Cryptophractus Fitzinger, 1856

Abstract: The hairy long-nosed armadillo, currently referred as Dasypus (Cryptophractus) pilosus, is an enigmatic species endemic to montane cloud forests and subparamo of Peruvian Andes. Its strikingly different external features, which include the carapace concealed by abundant hair, the presence of more movable bands, and a slender skull, have raised questions regarding its taxonomic status as subgenus or as genus. This paper assesses this issue based on a cladistic study and provides a detailed comparative descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
3
18

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(53 citation statements)
references
References 29 publications
0
32
3
18
Order By: Relevance
“…kappleri (sensu lato) is the sister taxon of all other Dasypus species, while D . pilosus is the last lineage to diverge, contrary to the results of Castro et al [6]. …”
Section: Resultscontrasting
confidence: 92%
See 3 more Smart Citations
“…kappleri (sensu lato) is the sister taxon of all other Dasypus species, while D . pilosus is the last lineage to diverge, contrary to the results of Castro et al [6]. …”
Section: Resultscontrasting
confidence: 92%
“…kappleri with extinct Propraopus and Dasypus bellus , and suggested that they belong to the same taxon, recognizable either as a subgenus or genus. Castro et al [6] proposed recognizing D . (Crypthophractus) pilosus as a distinct monotypic genus, based on its exclusive traits and its external position in their cladistic morphological analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the Dasypodinae mostly have a poor hair development (except for Cryptophractus pilosus, a species located in very high areas in the Peruvian Andes, see Castro et al 2015), while Euphractinae have a greater hair development and large deposits of adipose tissue, which could provide a greater thermal insulation and reduction in the thermal conductance. In turn, the greater glandular development in Euphractinae could be associated with more arid and harsher environments with drier and sandier soils, which would involve a greater necessity of substances to maintain the ectodermic structures moist.…”
Section: Biogeographic Distribution and Morphological Distinctivenessmentioning
confidence: 99%